2003
DOI: 10.1007/s00464-002-8584-5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical smoke: a review of the literature

Abstract: Surgical smoke is omnipresent in the day-to-day life of the surgeon and other medical personnel who work in the operating room. In addition, patients are also exposed, especially and uniquely so in laparoscopic cases where smoke is created and trapped in a closed and absorptive space. Surgical smoke has typically been produced by electrocautery but is now ever more present in a new form with the burgeoning use of the laser and the harmonic scalpel. Several cases of transmission of human papillomavirus (HPV) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
358
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(374 citation statements)
references
References 63 publications
(72 reference statements)
3
358
0
7
Order By: Relevance
“…However, there is a risk and hence measures should be taken to minimize the exposure as much as is possible [37][38][39].…”
Section: Other Constituent Of Surgical Smokementioning
confidence: 99%
“…However, there is a risk and hence measures should be taken to minimize the exposure as much as is possible [37][38][39].…”
Section: Other Constituent Of Surgical Smokementioning
confidence: 99%
“…The generation of a surgical plume is harmful when it persists as it decreases visualization, often requiring the surgeon to remove the scope from the surgical field and remove the obstructing aerosol particles. Compromised visualization in endoscopic surgery could be dangerous and fatal [9,10]. There are a lot of studies on the effects on the composition of surgical smoke and its effects on the operating theater personnel [10].…”
Section: Analysis Of Obstruction Generated By Laparoscopic Dissectorsmentioning
confidence: 99%
“…Plume aerosol generated by ultrasonic dissectors can be identified up to 40 cm from the point of production and usually is composed of tissue, blood, and blood products. The surgical plume production from an ultrasonic scalpel was compared with that from electrocautery by Ott et al [13], which described large quantities of cellular debris ([1 9 107 particles/mL) in the plume generated by the ultrasonic scalpel but had approximately one-fourth the amount of particle concentration which was further substantiated in the review exclusively on surgical smoke wherein the instrument and its effect on different types of tissue was also described [9,13]. Fatty tissue was found to generate 17-23 times more particles than lean tissue did [13].…”
Section: Analysis Of Obstruction Generated By Laparoscopic Dissectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research has also demonstrated that the temperatures produced by electrosurgical techniques can also create various end products. For example, higher cautery temperatures produce greater amounts of hazardous chemical components in the smoke; lower temperatures produce more cell particles (Barrett & Garber, 2003). Research has also revealed that different electrosurgical techniques produce different amounts of surgical smoke.…”
mentioning
confidence: 99%